2020
DOI: 10.5194/acp-20-15983-2020
|View full text |Cite
|
Sign up to set email alerts
|

Long-term deposition and condensation ice-nucleating particle measurements from four stations across the globe

Abstract: Abstract. Ice particle activation and evolution have important atmospheric implications for cloud formation, initiation of precipitation and radiative interactions. The initial formation of atmospheric ice by heterogeneous ice nucleation requires the presence of a nucleating seed, an ice-nucleating particle (INP), to facilitate its first emergence. Unfortunately, only a few long-term measurements of INPs exist, and as a result, knowledge about geographic and seasonal variations of INP concentrations is sparse.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 91 publications
11
28
0
Order By: Relevance
“…For instance, the measured N BAC values fall within the estimated range of bacterial cell concentrations for forest ecosystems (i.e., 3.3-8.8 × 10 4 m −3 ) according to Burrows et al (2009a). Furthermore, a predominance of Eukaryotes in the Amazon was shown by Souza et al (2019) and Elbert et al (2007), which is consistent with our results. Of further atmospheric relevance is the number concentration of all airborne cells that were determined by staining the intracellular DNA with the fluorescent dye DAPI 1 (N DAPI ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, the measured N BAC values fall within the estimated range of bacterial cell concentrations for forest ecosystems (i.e., 3.3-8.8 × 10 4 m −3 ) according to Burrows et al (2009a). Furthermore, a predominance of Eukaryotes in the Amazon was shown by Souza et al (2019) and Elbert et al (2007), which is consistent with our results. Of further atmospheric relevance is the number concentration of all airborne cells that were determined by staining the intracellular DNA with the fluorescent dye DAPI 1 (N DAPI ).…”
Section: Resultssupporting
confidence: 90%
“…The genome sizes were determined as follows. Souza et al (2019) found Proteobacteria and Actinobacteria to be the dominant phyla within the airborne Amazonian bacterial population. The median genome sizes found in the National Center for Biotechnology Information (NCBI) database were ∼ 4.8 and ∼ 4.3 Mb for Proteobacteria and Actinobacteria, respectively (https://www.ncbi.nlm.nih.…”
Section: Quantification Of Atmospheric Dna Concentrationmentioning
confidence: 93%
“…SDE tracers, this is specially relevant for sites where the presence of dust events is inferred from the α SSA alone, as has been done in previous studies at the JFJ (Chou et al, 2011;Boose et al, 2016a;Lacher et al, 2018a). INP concentrations shows a leptokurtic log-normal distribution, which is consistent with the theory by Ott (1990) and other studies (e.g., Welti et al, 2018;Schrod et al, 2020 Since SDEs consist only of the high concentration tail of the log-normal distribution of dust in the atmosphere after successive random dilution by large and small scale dynamics, also visible in the dust CAMS frequency distribution in Figure 6b, it is likely that ice-active dust is also present outside of SDE periods, however in smaller concentrations. For the following assessment, we assume that a constant mass-fraction of all dust carried to the JFJ will act as INPs.…”
Section: Particulate Matter Measurementssupporting
confidence: 88%
“…To capture and study this effect, design adaptations need to be implemented in our sampling equipment in upcoming studies, as the pore ice sublimates or melts in the heated and dried sampling lines upstream of the INP counter used here. studies (e.g., Welti et al, 2018;Schrod et al, 2020). We found dust to be the main contributor to the INP population at 243.15 K and S w = 1.04 at the JFJ, with 74.7 ± 0.2% of all INPs observed during SDEs.…”
Section: Backtracking Sdes With the European Ceilometer Networkmentioning
confidence: 50%
“…At the ATTO site, the first aerosol measurements were initiated in 2011 (e.g., Pöhlker et al, 2012;Saturno et al, 2018b). Since 2014, multiple continuous measurements of physical and chemical particle properties have been established and gradually extended (e.g., Pöhlker et al, 2016Pöhlker et al, , 2018Holanda et al, 2020;Saturno et al, 2018a;Schrod et al, 2020).…”
Section: Introductionmentioning
confidence: 99%